A comparison of the prevalence and severity of health problems in national team cross-country skiers over a competitive season - Karlsson, Ø.; Danemar, M.; Laaksonen, M. S.; McGawley, K. (British Journal of Sports Medicine, 2021)
Background A limited number of long-term prospective studies have investigated health problems in competitive cross-country skiers. Moreover, limited information exists regarding differences in the prevalence and severity of health problems between senior and development female and male cross-country skiers.